2021
DOI: 10.3389/fmed.2021.721953
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Composition of the Uveal Immune Environment

Abstract: The uveal tract consists of the iris, the ciliary body and the choroid; these three distinct tissues form a continuous layer within the eye. Uveitis refers to inflammation of any region of the uveal tract. Despite being grouped together anatomically, the iris, ciliary body and choroid are distinct functionally, and inflammatory diseases may affect only one part and not the others. Cellular structure of tissues direct their function, and understanding the cellular basis of the immune environment of a tissue in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 138 publications
1
8
0
Order By: Relevance
“…2B). In agreement with previous immunohistological studies [ 9 ], we found that myeloid cells including monocytes, macrophages, neutrophils and mast cells contributed to the majority of the immune cell population in the ciliary body (Fig. 1 A, B , Suppl.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…2B). In agreement with previous immunohistological studies [ 9 ], we found that myeloid cells including monocytes, macrophages, neutrophils and mast cells contributed to the majority of the immune cell population in the ciliary body (Fig. 1 A, B , Suppl.…”
Section: Resultssupporting
confidence: 93%
“…One of the major cell types identified was the macrophage population, supporting the notion that cells of the myeloid lineage primarily make up the immune repertoire of the healthy uveal tract [ 9 ]. The ciliary body has been recognized to have an immunosuppressive environment [ 9 , 66 ], and the anti-inflammatory (M2) macrophages are important for the maintenance of such an immune status.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The presence of ciliary body lymphatics has also been investigated by several other groups; however, the results were conflicting. One consistent finding of these studies was the presence of LYVE1-positive cells in the ciliary body stroma and processes [ 74 , 75 , 76 , 77 ]. Interestingly, the majority of these cells was also immunoreactive for CD68 (a well-known macrophage marker), indicating that these cells might belong to the macrophage lineage [ 75 ].…”
Section: Lymphatic Systemmentioning
confidence: 66%